Effect of contour interval on minimization of tool path length in pocket milling process - Abdullah, Haslina; Ramli, Rizauddin; Abd Wahab, Dzuraidaqh (Taylor's University, 2020)
Reduction of machining time in the pocket machining process is important in order to enhance performance and increase productivity. In this paper, the main objective is to decrease the roughing time in pocket milling process by investigating the effect of path interval caused by the uncut area in the pocket milling with sharp corner. Decreasing machining time in process of milling using contour parallel direction as a strategy of machining can be achieved by increasing the value of tool path interval. Though, increasing the tool path interval has caused the existence of an uncut area at the sharp corner. To remove this uncut area, an additional tool path length is generated. So, this paper is carried out to study the consequence of path interval upon the existence of uncut region and the impact to the path length of contour parallel. There were three different values of tool path interval chosen and set to study the consequence of cutting tool path interval on tool path length, which were 5.6 μm, 5.7 μm, and 5.9 μm. Ant colony algorithm was developed to minimise the additional path length. As a result, increasing the path interval has produced larger uncut region at the corner. However, it produced shorter additional tool path length which resulted in lower roughing time.